Impact of prime-age adult mortality on labor supply: Evidence from adolescents and women in South Africa - Yamauchi, Futoshi; Buthelezi, Thabani; Velia, Myriam (International Food Policy Research Institute, 2008)
The recent dramatic increase in prime-age adult mortality in many African countries is largely attributed to the AIDS epidemic. Excess mortality is concentrated among women between the ages of 25 and 39 and among men between the ages of 30 and 44. Households can respond to an increase in mortality among prime-age adults in many ways—they can utilize government grants and formal insurance; engage in some ex ante and ex post risk coping/mitigating strategies (e.g., borrowing or tapping on remittances) to buffer shocks; and/or develop foster-care arrangements or income diversification strategies (including labor supply). There are, however, problems with these approaches. If such strategies are imperfect in smoothing consumption, prime-age adult death can decrease child schooling investments and increase labor supply, at least in the short-run. Moreover, prime-age adult death also reduces the expected future earnings for the household. This, in turn, reduces investments in child schooling, given that the period over which capital is formed is long and the loan market is imperfect. Typically, the growth in the number of orphans in a society is taxing on both families and the society and an increase in mortality among prime-age adults, unlike mortality in other age groups, directly reduces the capability of households to secure income.